PENDEKATAN SOSIO-HISTORIS: Alternatif dalam Memahami Perkembangan Ilmu Kalam - Djazimah, Nurul (Jurnal Ilmu Ushuluddin, 2012)
This paper studies about the developing of ilm kalam. As for the writer, there aremany historical events that colored the muslimâs thought in field of ushuluddin. Thestatus of islamic theology (faith) in the period of the Prophet and his companions werevery different with the mutakkiliminâs thought in next century. The expression and thediscussion and the argumentations were submitted is really different between propheticperiod and mutakklimin one. Even, in the body of mutakkalimin its self there areseveral models in expression and argumentation. This reality was caused by manyfactors and conditions. By seeing the developing of ilm ushuluddin time by time, can beconcluded that the thought of intelectual muslim in last time was relevant with thechallange in that time. It means that in our period today where the the science and thetechnology evolved rapidly, needed the new model of ilm tauhid that relevant with thesituation and the condition today. So that, the world of God (ayat kauniyyah) that wemay find in many verses in Alquran must be learned in particular.